Libido parameters and their correlation with seminal characteristics in Jakhrana bucks maintained under different systems - KUMAR, NARENDRA; RAI, B; GANGWAR, CHETNA; KUMAR, ANSHUMAN; KHARCHE, S D; LONE, S A; JINDAL, S K (The Indian Journal of Animal Sciences, 2016)
Jakhrana bucks (24) of the same body weight (BW, 30±2 kg) and age (12±0.5 month) were selected to study libido parameters and their correlation with seminal characteristics. The bucks were randomly allotted into group 1 (intensive system, 12 bucks) and group 2 (semi-intensive system, 12 bucks) under group feeding management conditions. Ejaculates (336; 168 from each group) were collected twice weekly and evaluated for various seminal characteristics (volume, pH, mass motility, progressive motility, concentration, viability, hypo-osmotic swelling (HOS) response and acrosomal integrity). The libido parameters (reaction time, refractory period, mounting enthusiasm, erection status of penis and fixing strength of male) were recorded from each group and it was synchronized with semen collection. No significant correlation was observed between libido parameters and semen characteristics. However, significant negative correlation was observed between semen volume with reaction time and refractory period, respectively. Moreover, libido parameters between groups 1 and 2 did not show a significant difference. It may be concluded that there is no correlation between libido parameters and seminal characteristics (except semen volume), so it may be possible to obtain good semen samples from bucks with low libido.